Microstructural evaluation of gas nitrided AISI 316 LN austenitic stainless steel. (2022) - Arun Prasad, M.; Dharmalingam, G.; Salunkhe, Sachin
Abstract: Direct utilization of austenitic stainless steel is limited in numerous industries due to its low surface hardness. To improve the hardness of steels, gas nitriding is a convenient technique to enhance the surface hardness of austenitic stainless steel (316 LN). AISI 316 LN austenitic grade stainless steel were utilized for various applications like nuclear cladding tubes, heaters, turbine parts and blower parts. Nitiriding was carried out for three different hours namely 14, 24 and 72 hrs for the austenitic stainless in the current study. A maximum surface hardness of 1200 HV is obtained for gas nitirding technique when compared to 210 HV for the untreated specimen. Gas nitrided specimen shows a uniform nitride layer on the 316 LN stainless steel. Similarly XRD analysis of the nitrided specimen unveil the distribution of iron nitride phase which occurred during nitriding process. An effective case depth of the compounded layer from gas nitriding was found to be 30.7 µm.